MK2461, a Multitargeted Kinase Inhibitor, Suppresses the Progression of Pancreatic Cancer by Disrupting the Interaction Between Pancreatic Cancer Cells and Stellate Cells. Issue 4 (April 2017) - Inoue, Koetsu; Ohtsuka, Hideo; Tachikawa, Masanori; Motoi, Fuyuhiko; Shijo, Masahiro; Douchi, Daisuke; Kawasaki, Shuhei; Kawaguchi, Kei; Masuda, Kunihiro; Fukase, Koji; Naitoh, Takeshi; Katayose, Yu; et al.
Abstract : Objectives: Platelet-derived growth factor receptor beta (PDGFRβ) and hepatocyte growth factor receptor (MET) expressed on pancreatic stellate cells (PSCs) are suggested as important components modulating the interactions between pancreatic cancer cells (PCCs) and PSCs. The objective of this study is to clarify the effect of MK2461, a multikinase inhibitor targeting MET and PDGFRβ, on the interaction between PCCs and PSCs. Methods: In this study, we profiled the expression of receptor tyrosine kinases (including PDGFRβ and MET) in pancreatic cancer with quantitative targeted absolute proteomics using liquid chromatography tandem mass spectrometry. In addition, the effect of MK2461 on PCC-PSC interaction was investigated using PSCs prepared from pancreatic cancer tissues. Results: In PSCs, PDGFRβ and MET were upregulated compared with other receptor tyrosine kinases. Conditioned medium from PSCs promoted the proliferation of PCCs, and vice versa. Moreover, MK2461 suppressed the effects of conditioned medium on PCCs and PSCs. Finally, MK2461 significantly inhibited tumor growth in mice coinjected with PCCs and PSCs. Conclusions: The PDGFRβ and MET may play a critical role in the interaction between PCCs and PSCs, which was modulated by MK2461. Therefore, MK2461 may have therapeutic potential in the treatment of pancreatic cancer. Abstract : Supplemental digital content is available in the text.